GREEN BUYING BEHAVIOR AMONG MAURITIAN CONSUMERS: EXTENDING THE TPB MODEL : Received: 28th June 2021; Revised: 25th October 2021, 11th January 2022, 21st January 2022; Accepted: 25th January 2022 - Gungaphul, Mridula; Heeroo, Soheenee Devi (PEOPLE: International Journal of Social Sciences, 2022)
This study aims to explore the major predictors of green purchase behavior in Mauritius, using an extension of the Theory of Planned Behavior (TPB) model by incorporating advertising and sales promotion as two new factors. A self-administered questionnaire using quota and judgmental sampling survey was conducted to collect data. Hundred and fifty respondents judged to be knowledgeable about environmentally friendly products were approached to participate in the survey. The findings reveal that Mauritians have a strong positive attitude towards the environment. Sales promotion, subjective norms, and attitude towards the environment are found to be significant determinants of green purchase intention. Perceived behavioral control and advertising were identified as not very significant variables. Results further show that there is not enough advertising done concerning green products in Mauritius. A positive relationship between green purchase intention and green purchase behavior was also identified. The results of this study can assist marketers and policymakers in developing more effective strategies when marketing green products in Mauritius to create better awareness and more acceptability of this emerging phenomenon that is a good part of sustainability development.